Reworking the Social Determinants of Health: Responding to Material‐Semiotic Indeterminacy in Public Health Interventions. (27th June 2020) - Yates‐Doerr, Emily
Abstract: Both public health experts and medical anthropologists are concerned with how health is shaped by environmental forces. This creates an important cross‐disciplinary alliance, yet crucial differences in how the two disciplines tend to evaluate health remain. In this article, I compare public health's "social determinants of health" framework with anthropological interest in the sociality of health and illness. I draw on ethnographic fieldwork in Guatemala's highlands, to unpack (1) "the social, " (2) "determinants, " and (3) "of health." Ultimately, I show how the social determinants framework is deployed in ways that risk undermining its stated health justice goals, and highlight the benefits of an approach that does not know what health is ahead of doing research and which works closely with communities to respond to the effects of its own intervention. The article argues for the need to rework the emphasis on social determinants to make space for health's material‐semiotic indeterminacy